2008
DOI: 10.1021/je800564d
|View full text |Cite
|
Sign up to set email alerts
|

Liquid−Liquid Equilibria for Castor Oil Biodiesel + Glycerol + Alcohol

Abstract: Phase equilibrium behavior of the system castor oil biodiesel + glycerol + methanol was studied to provide experimental data for the optimization of the separation downstream processes. Measurements of solubility were carried out for the ternary systems containing biodiesel derived from castor + glycerol + methanol at 298.15 K and + ethanol at (298.15 and 333.15) K. An increase of the system mutual solubility was observed with temperature. Binodal curves were determined by the cloud point using the titration m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
5
39
0
2
Order By: Relevance
“…Since ethanol increases the solubility of glycerol in the biodiesel phase, it can likely lead to separation difficulties in transesterification process. In this sense, although there is a growing industrial interest in the separation processes related to the production of components of fatty acid ethyl esters biodiesel, there are few experimental data regarding the ethyl ester, fatty acid, ethanol, water and/or glycerol available in the open literature [1,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Most [17,18] and ethyl palmitate + ethanol + glycerol [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since ethanol increases the solubility of glycerol in the biodiesel phase, it can likely lead to separation difficulties in transesterification process. In this sense, although there is a growing industrial interest in the separation processes related to the production of components of fatty acid ethyl esters biodiesel, there are few experimental data regarding the ethyl ester, fatty acid, ethanol, water and/or glycerol available in the open literature [1,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Most [17,18] and ethyl palmitate + ethanol + glycerol [19].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that, in the temperature range covered in this work (303.2-323.2 K), the effect of temperature is not significant on decreasing the biphasic region. This behaviour has been also observed for ternary mixtures involving biodiesel and glycerol together with different alcohols [17][18][19]. This means that the reaction temperature of the glycerolysis system can be determined in terms of kinetic parameters rather than in order to increase the mutual solubility of reactants.…”
Section: Experimental Datamentioning
confidence: 66%
“…Na indústria de produção do biodiesel, dados de equilíbrio líquido-líquido podem ser usados para compreender os processos de separação e purificação das fases ricas em biodiesel e em glicerol. 23 Trabalhos envolvendo sistemas ternários com uso de biodiesel, semelhantes ao da nossa proposta, 21,[23][24][25][26][27][28][29] são apresentados na Tabela 1S, disponível no Material Suplementar.…”
Section: Fundamentação Química Da Atividade Propostaunclassified
“…No experimento, a variável é o biodiesel a ser utilizado, que pode produzir resultados novos a cada experimento, dependendo da origem do óleo vegetal e das condições de síntese e purificação do mesmo. Esta variável permite, como se pode ver pelos diferentes diagramas ternários citados neste trabalho, 21,[23][24][25][26][27][28][29] que resultados diferentes sejam adquiridos nos diferentes experimentos. Esta prática faz com que os alunos não se limitem a um roteiro experimental previamente estabelecido.…”
Section: Conclusõesunclassified